An uncommon cause of fever in a patient with hyperthyroidism - Krishna P Gautam; Kanakkankotil U Lijesh; John Jude; Riddhi D Gupta; Thomas V Paul (Journal of Family Medicine and Primary Care, 2020)
Fever as an indicator of disease has always been and remains a clinical symptom of great importance. It may be a manifestation of any inflammatory process of the thyroid and also may be presenting feature of thyroid storm. Melioidosis, is an infection caused by the gram negative bacterium Burkholderia pseudomallei and the commonest co-morbidity observed in India is diabetes mellitus. Here we present a case of Graves disease (hyperthyroidism) who was referred by primary care physician with history of prolonged fever of more than one month duration and later diagnosed to have melioidosis. It is important in primary care setting as family physicians need to be aware of this infection as it can affect many organs and early diagnosis and treatment will result in cure of this condition.